The Benefits of Swimming on the Lungs Vital Capacity - Hadiansyah, Muhammad Chanifuddin; Hartono, Ameilia Sawitri; Prakoso, Bagas Wahyu; Ardiansyah, Farid Nur; Billiandri, Bhayu (Universitas Negeri Semarang, 2022)
Sport is an activity that is useful to nourish the individual body physically and spiritually. Health is an important need and has a major role in survival. Physical health or also called physical fitness has a vital contribution in indicators of a person's overall health status. Through descriptive-qualitative research method by collecting secondary and primary data from several journals. Swimming is a sport that is a form of water sports. Swimming is also a water aerobics sport, where this sport requires a lot of oxygen input. The benefits of this swimming sport are on the respiratory system. The respiratory system is one of the systems found in the individual's body that plays an important role in the process of life. In swimming, which is an aerobic exercise that requires a lot of oxygen, this affects the vital capacity of the lungs. The vital capacity of the lungs is the maximum amount of oxygen that enters the lungs. So that by doing swimming regularly, the vital capacity of the lungs will be better.